Penanaman Jiwa Entrepreneuiship Melalui Pembelajaraan IPS Tingkat Dasar - M. Irfan Mahmudi; Badrus Badrus (Institut Agama Islam Tribakti Kediri, 2022)
The development of subject-based learning strategies integrated with entrepreneurship has become a new awareness in basic Islamic education. Children are not only required to be sensitive to business opportunities. Interestingly, many basic Islamic educational institutions have tried to implement it, but have not attracted much interest from researchers. The reason, the phase or stages of child development, is not yet feasible to understand the spirit of entrepreneurship. In this context, this research uses qualitative methods to get a more comprehensive and in-depth picture of the application of learning to increase the entrepreneurial spirit in Islam as if it were the basis of Islam. The data generated are the results of interviews, periodic field observations and document studies in accordance with the research focus. During data mining, the researcher simultaneously analyzed and condensed the data to be presented in the research report. The results of this study indicate that, 1) the design of entrepreneurship learning for upper-class students at MI Al Karim Gondang uses a fairly complete step, namely: 1) setting learning objectives in words that are operational and easy to understand for students, 2) determining the form of practice, with details a) using concrete materials, in the school environment. b) using visual tools, pictures, real materials, c) using examples that have been understood by students. d) Presenting material in an organized manner, starting from understanding, examples, and increasing to more detailed (complicated) material, e) providing exercises with various methods. f) contextual assignment of tasks, g) determine the form of process and outcome evaluation. The results of the second study (2) The implementation of entrepreneurship cultivation in Social Sciences (IPS) learning is carried out by a) introducing money, the function of money, saving and how to get it, b) conducting observations on local tofu and tempeh business products, the practice of planting flowers and fruit in madrasas and participate in organizing marked day [Pengembangan strategi pembelajaran berbasis mata pelajaran terintegrasi dengan entrepreneurship menjadi kesadaran baru dalam pendidikan Islam dasar. Anak-anak tidak hanya dituntut untuk mempunyai keperkaan terhadap peluang bisnis. Menariknya, banyak lembaga pendidikan Islam dasar berusaha menerapkan, akan tetapi tidak banyak menarik minat peneliti. Alasannya, fase atau tahapan perkembangan anak, belum layak untuk memahami jiwa entrepreneurship. Dalam koteks ini, penelitian ini menggunakan metode kualitatif untuk mendapatkan gambaran lebih menyeluruh dan mendalam tentang penerapan pembelajaran meningkatkan jiwa entrepreneurship di seolah dasar Islam. Data-data yang dihasilkan merupakan hasil wawancara, observasi lapangan secara berkala dan studi dokumen sesuai dengan fokus penelitian. selama penggalian data, secara bersamaan peneliti melakukan analisis dan kondensasi data untuk disuguhkan dalam laporan hasil penelitian. Hasil penelitian ini menunjukkan bahwa, 1) desain pembelajaran entrepreneurship pada peserta didik kelas atas MI Al Karim Gondang menggunakan langkah yang cukup lengkap yakni: 1) menetapkan tujuan pembelajaran dengan kata yang operasional dan mudah dimengerti peserta didik, 2) menetapkan bentuk praktiknya, dengan rincian a) menggunakan bahan-bahan yang konkret, di lingkungan sekolah. b) menggunakan alat visual, gambar, bahan nyata, c) menggunakan contoh yang sudah dimengerti peserta didik . d) Menyajikan materi dengan terorganisir, mulai dari pengertian, contoh, dan meningkat ke materi yang lebih detail (rumit), e) memberikan latihan dengan berbagai metode. f) pemberian tugas secara kontekstual, g) menetapkan bentuk evaluasi proses dan hasil. Hasil penelitian yang kedua (2) Implementasi penanaman entrepreneurship pada pembelajaran Ilmu Pengetahuan Sosial (IPS) dilakukan dengan a) mengenalkan uang, fungsi uang, menabung dan cara mendapatkanya, b) mengadakan obsevasi ke produk usaha lokal tahu dan tempe, praktik penanaman bunga dan buah di madrasah dan ikut menyelenggarakan marked day]